Semi-Supervised Learning for Glomerular Crescent Classification - Silva, Joacy M. da; Santos, Washington L. C. dos; Duarte, Angelo A.; Oliveira, Luciano R. de; Angelo, Michele F.; Loula, Angelo C. (Anais Estendidos da Conference on Graphics, Patterns and Images (SIBGRAPI), 2025)
Glomeruli, the fundamental structures of the kidney responsible for blood filtration, are susceptible to various pathologies, including glomerular crescents. This work investigates the application of semi-supervised deep learning (SSL) for the classification of histopathological images containing these lesions. We evaluate several configurations of a deep learning model for classifying crescent versus normal glomeruli. Our investigation specifically compares the impact of varying the ratio of labeled to unlabeled data and the effect of different input perturbations (e.g., Random Flip + Random Crop) on model performance. Based on accuracy, precision, sensitivity, and F1-score, the model trained with four labeled folds and using Random Flip + Random Crop perturbations emerged as the most effective configuration. In a separate experiment, we expanded the classification task to distinguish crescent from non-crescent glomeruli by adding images of three other lesion types to the dataset. Our results show that a combined training approach using Mean-Teacher and Supervised Contrastive Learning (SCL) did not yield significant performance improvements compared to the model trained solely with the Mean-Teacher method.